2019
DOI: 10.1007/s42399-019-00165-3
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Due to Ignatzschineria ureiclastica Caused by Maggot-Infested Wounds in a Homeless Man in Germany: a Case Report

Abstract: The gram-negative rod bacteria Ignatzschineria inhabits the digestive tract of larvae and adult forms of flesh flies and mostly causes bloodstream infections in animals, but rarely in humans with chronic wounds. This is the second case report of sepsis due to Ignatzschineria ureiclastica worldwide and the first reported case of Ignatzschineria species in Germany. We present a case report of 57-year-old homeless male with chronic leg and foot ulcers with maggot infestation. Blood cultures revealed gramnegative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Of note, Le Brun et al described a case of Ignatzschineria-associated septicemia arising in a clinical scenario very similar to our case, with the isolate identified only to the genus level, as 16S rRNA sequencing showed homology identical to that of both I. larvae (99%) and I. ureiclastica (99%) (10). There has been one reported case of sepsis due to I. ureiclastica in which a 99.7% 16S rRNA sequence homology was observed to the original I. ureiclastica (FFA3 T ) GenBank isolate reported by Gupta et al (11). To our knowledge, there are no definitive prior case reports of I. larvae infection in humans, although there are several reports in which species-level identification could not be reliably performed.…”
Section: Discussionsupporting
confidence: 84%
“…Of note, Le Brun et al described a case of Ignatzschineria-associated septicemia arising in a clinical scenario very similar to our case, with the isolate identified only to the genus level, as 16S rRNA sequencing showed homology identical to that of both I. larvae (99%) and I. ureiclastica (99%) (10). There has been one reported case of sepsis due to I. ureiclastica in which a 99.7% 16S rRNA sequence homology was observed to the original I. ureiclastica (FFA3 T ) GenBank isolate reported by Gupta et al (11). To our knowledge, there are no definitive prior case reports of I. larvae infection in humans, although there are several reports in which species-level identification could not be reliably performed.…”
Section: Discussionsupporting
confidence: 84%
“…Ignatzschineria bacteremia is often associated with poor living or working conditions, alcoholism, open wounds/ulcers, and peripheral vascular disease [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . It was reported that this patient had been living in poor conditions in a basement and had also shown behaviors of self-neglect both of which predisposed him to myiasis and therefore Ignatzschineria infection.…”
Section: Discussionmentioning
confidence: 99%
“…The organism identified in this case was determined to be most genetically similar to I. larvae and I. ureiclastica, both of which are rarer when compared to I. indica . While there have been 11 cases of I. indica reported, there have been only three cases of I. larvae and two cases of I. ureiclastica [1] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [13] , [15] , [16] , [18] , [20] , [21] . In addition, I. indica is the only species to have been reported in North America [7] , [8] , [10] , [11] , [15] , [17] , [20] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations